Multiple Gastrointestinal Complications of Crack Cocaine Abuse. (15th April 2014) - Carlin, Neal; Nguyen, Nhat; DePasquale, Joseph R.
Abstract : Cocaine and its alkaloid free base "crack-cocaine" have long since been substances of abuse. Drug abuse of cocaine via oral, inhalation, intravenous, and intranasal intake has famously been associated with a number of medical complications. Intestinal ischemia and perforation remain the most common manifestations of cocaine associated gastrointestinal disease and have historically been associated with oral intake of cocaine. Here we find a rare case of two relatively uncommon gastrointestinal complications of hemorrhage and pancreatitis presenting within a single admission in a chronic crack cocaine abuser.